Nexus between environmental sustainability, good governance, financial inclusion, and tourism development in Bangladesh: Evidence from symmetric and asymmetric investigation - Islam, Yeasmin; Mindia, Piana Monsur; Farzana, Nusrat; Qamruzzaman, Md (Frontiers in Environmental Science, 2023)
Over the past decade, tourism’s contribution to economic Section progress has emerged as an alternative avenue for socio-economic development, especially in the productive economy with natural beauty. On the other hand, the potential effects of tourism on the environment have also been unveiled in the literature, along with macroeconomic misbehavior due to erratic environmental changes. However, the study’s impetus is to inspect the reaction of tourism contribution to Bangladesh’s economy from 1991–2019 with ecological sustainability, good governance, and financial inclusion in the empirical assessment. With the implementation of both linear and non-linear frameworks, the present study has explored the elasticities of core explanatory variables on explained variables; for directional causality, the novel Fourier Toda and Yamamoto causality test has been executed. According to the combined cointegration test, Bangladesh has a long-run association between environmental sustainability, good governance, financial inclusion, and tourism development. Inferring from long-run symmetric and asymmetric cointegration, the test statistics revealed statistically significant at a 1% level, suggesting the long-run relations in the established empirical model. Considering the linear autoregressive disoriented lagged, the study established a negative and statistically significant linkage between environmental sustainably and tourism contribution, suggesting that the excessive inflows of carbon emission that environmental degradation dwindles the progress of tourism contribution. Whereas a positive and statistically significant influence runs from good governance and financial inclusion to tourism development, the suggestion of easy access to financial services and effective institutional activities prompts tourism activities, especially in the long-run. The asymmetric investigation established non-linearity in the empirical model for the long and short-run. In terms of asymmetric coefficients, the study unveiled the positive and negative shocks of environmental sustainability exposed negatively and statistically significant. In contrast, the asymmetric shocks of financial inclusion and good governance established positive and statistically substantial Bangladesh tourism development in the long and short-run. The directional causality assessment revealed bidirectional causality running between explanatory variables to tourism development.